Improving quality of care through patient-reported outcome measures (PROMs): expert interviews using the NHS PROMs Programme and the Swedish quality registers for knee and hip arthroplasty as examples - Birgit Prodinger; Paul Taylor (BMC, 2018)
Abstract Background Patient reported outcome measures (PROMs) have been integrated in national quality registries or specific national monitoring initiatives to inform the improvement of quality of care on a national scale. However there are many unanswered questions, such as: how these systems are set up, whether they lead to improved quality of care, which stakeholders use the information once it is available. The aim of this study was to examine supporting and hindering factors relevant to integrating patient-reported outcome measures (PROMs) in selected health information systems (HIS) tailored toward improving quality of care across the entire health system. Methods First, a systematic search and review was conducted to outline previously identified factors relevant to the integration of PROMs in the selected HIS. A social network analysis was performed to identify networks of experts in these systems. Second, expert interviews were conducted to discuss and elaborate on the identified factors. Directive content analysis was applied using a HIS Evaluation Framework as the frame of reference. This framework is structured into four components: Organization, Human, Technology, and Net benefits. Results The literature review revealed 37 papers for the NHS PROMs Programme and 26 papers for the SHPR and SKAR: Five networks of researchers were identified for the NHS PROMs Programme and 1 for the SHPR and SKAR. Seven experts related to the NHS PROMs Programme and 3 experts related to the SKAR and SHPR participated in the study. The main themes which revealed in relation to Organization were Governance and Capacity building; to Human: Reporting and Stakeholder Engagement; to Technology: the Selection and Collection of PROMs and Data linkage. In relation to Net benefits, system-specific considerations are presented. Conclusion Both examples succeeded in integrating PROMs into HIS on a national scale. The lack of an established standard on what change PROMs should be achieved by an intervention limits their usefulness for monitoring quality of care. Whether the PROMs data collected within these systems can be used in routine clinical practice is considered a challenge in both countries.